2019
DOI: 10.1051/matecconf/201928309003
|View full text |Cite
|
Sign up to set email alerts
|

The acoustic insulation performance of infinite and finite locally resonant metamaterial and phononic crystal plates

Abstract: The bending wave stop band behavior of locally resonant metamaterial and phononic crystal plates can strongly improve the vibration performance of flexible plates in targeted frequency ranges. Their acoustic insulation performance, however, is found to strongly depend on the stop band mechanism, also influencing the frequency range of improvement. While sound transmission loss improvements are predicted for both infinite periodic plates, the finite phononic crystal plate performance can differ significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
3
4
0
Order By: Relevance
“…Besides disappearing STL improvements, further increasing f res also leads to broadening zones of reduced STL after the STL peak, which is undesirable for noise reduction. Similar deviations between predicted infinite and finite plate STL performance enhancements were also found for the phononic crystal plate with periodic point mass additions in [23].…”
Section: Sound Transmission Losssupporting
confidence: 76%
See 2 more Smart Citations
“…Besides disappearing STL improvements, further increasing f res also leads to broadening zones of reduced STL after the STL peak, which is undesirable for noise reduction. Similar deviations between predicted infinite and finite plate STL performance enhancements were also found for the phononic crystal plate with periodic point mass additions in [23].…”
Section: Sound Transmission Losssupporting
confidence: 76%
“…This STL peak for the infinite periodic plate is now predicted in absence of a stop band, in a frequency range in which bending modes are again allowed and in which local vibration suppression no longer amounts to global vibration reduction. Similar observations were made for a phononic crystal plate with periodic point-mass additions in [23] in which the STL peak emerged Fig. 5: STL of the infinite plates for varying f res , showing a clear STL peak for all considered f res , followed by an STL dip, regardless of the sub-wavelength criterion or presence of a bending wave stop band (dashed lines).…”
Section: Sound Transmission Losssupporting
confidence: 75%
See 1 more Smart Citation
“…The use of distributed resonators has also been investigated as an option to create MMs for both thin [23] and thick [24] plate structures using the plane wave expansion (PWE) method to achieve an improved sound transmission loss (STL). Furthermore, Van Belle et al have demonstrated [25] that both PCs and MMs are able to improve the STL of infinite plates. For MMs, this reduction occurs inside the band gap regions, due to sub-wavelength vibration suppression, while, for PCs, these occur outside the band gap regions due to specific vibration patterns.…”
Section: Introductionmentioning
confidence: 99%
“…By embedding resonant elements into a host structure, a material structure can be obtained, which shows stop band behavior in tunable frequency ranges, related to the natural frequency of the added resonant elements [4]. In these stop bands, no structural waves can freely propagate into the system, hence vibrations are attenuated, resulting in reduction of acoustic radiation and sound transmission [5,6,7]. Therefore, retaining low mass and low volume, locally resonant metamaterials can outperform the common NVH solutions, especially at the low frequency range.…”
Section: Introductionmentioning
confidence: 99%